2022
DOI: 10.1371/journal.pone.0273692
|View full text |Cite
|
Sign up to set email alerts
|

Advanced stage presentation and its determinant factors among colorectal cancer patients in Amhara regional state Referral Hospitals, Northwest Ethiopia

Abstract: Introduction Nowadays, the burden of colorectal cancer (CRC) has been increasing in the world, particularly in developing nations. This could be related to the poor prognosis of the disease due to late presentation at diagnosis and poor treatment outcomes. In Ethiopia, studies related to the stage of colorectal cancer at diagnosis and its determinants are limited. Therefore, the study was intended to assess advanced stage presentation and its associated factors among colorectal cancer patients in northwest Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The study revealed that 83.3% (95% CI: 79.4% -87.3%) of CRC patients were presented at an advanced stage of the disease. This nding is in line with the study conducted in Amhara Region at Felege Hiwot Comprehensive Specialized Hospital and the University of Gondar Hospital, which is 83.1% [10], and with the study conducted in Sokoto, Nigeria, which was 86.8% [18]. However, it is higher than studies conducted in Addis Ababa's Tikur Anbessa specialized hospital, which is 62.7% [19].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The study revealed that 83.3% (95% CI: 79.4% -87.3%) of CRC patients were presented at an advanced stage of the disease. This nding is in line with the study conducted in Amhara Region at Felege Hiwot Comprehensive Specialized Hospital and the University of Gondar Hospital, which is 83.1% [10], and with the study conducted in Sokoto, Nigeria, which was 86.8% [18]. However, it is higher than studies conducted in Addis Ababa's Tikur Anbessa specialized hospital, which is 62.7% [19].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, aged respondents were more likely to be prognosed to advanced stages than those who were not aged. This nding is supported by the study conducted in Amhara region hospitals and in the United States [10,23,24]. This could be due to the fact that as age increases, changes occur in the colon, such as mucosal changes, decreased motility, and reduced blood ow.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Patients in rural areas in Ethiopia often present with late-stage cancer, increasing the likelihood of needing an ostomy. 35…”
Section: Generalizabilitymentioning
confidence: 99%